Intervention study of Pilates combined with Baduanjin training on postpartum women with mild to moderate stress urinary incontinence - Du, Xiru; Liu, Yaoling (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Outline for the Development of Women and Children in China (2011-2020), calling on people from all walks of life to respect women and ensure women's access to basic medical and health services, life quality and health level. With the opening of China's three-child policy and the arrival of the aging population, it has a huge impact on China's economy. The incidence of stress urinary incontinence is increasing year by year, which seriously affects the quality of life of women. Kun Yu (2018) pointed out that the incidence of urinary incontinence in adult women is 31.3%, and the prevalence increases with age. Stress urinary incontinence is more common in middle-aged and elderly women and postpartum women, which causes pelvic floor muscle injury after childbirth. Studies by scholars at home and abroad have found that exercise intervention can improve stress urinary incontinence in mild and moderate patients, thus improving the quality of life of women. In severe patients, intervention by surgery or taking hormone drugs has no obvious improvement effect only through exercise intervention. Periodic literature searches with "pelvic floor muscles" as the theme and keywords from 2000 to 2021 have shown a linear upward trend in recent years. At the same time, a search of journal literature from 1980 to 2021 found that only 89 articles were published in sports journals, accounting for 1.09%. Moreover, most scholars' studies focused on medical rehabilitation, and there was certain room for improvement in the study of sports intervention. At present, the rehabilitation of mild to moderate stress urinary inence has the following forms: biofeedback electrical stimulation, laser irradiation, Kegel exercise, Chinese acupuncture point massage, ballet body training, yoga, Pilates, fitness Qigong and so on. Jianli Li (2013) pointed out that the practice of big dance hip swing combined with retroabdominal breathing of levator anus had a certain rehabilitation effect on the symptoms of stress urinary incontinence in women. Muying Zhong (2018) pointed out that Baduanjin had certain efficacy in improving postpartum stress urinary incontinence symptoms in women, but the sample size was small, and further exploration of this rehabilitation training was needed. Jiang Li (2019) pointed out that pelvic floor function training combined with moxibustion at Guanyuan acupoint can improve women's stress urinary incontinence, and proved that Chinese traditional medicine therapy can have a positive impact on pelvic floor muscle relaxation symptoms. The above research results of scholars provide research ideas for the creation of Pilates combined with Baduanjin training program. Pilates is an exercise that emphasizes muscle control. Practicing Pilates not only engages the large muscle groups, but also activates the deep smaller muscle groups. The traditional Baduanjin regimen has the function of regulating Qi and blood and tonifying kidney nourishing the liver. The practice of Baduanjin does not need specific equipment, is simple and easy to learn, and has good rehabilitation effect. As a treatment method, Baduanjin is widely used in the rehabilitation of chronic diseases. Pilates, on the other hand, involves lying on your back, on your side, or on your stomach, with fewer standing positions. Therefore, the use of Pilates combined with the training program of Baduan Kam, can be highly efficient and all-round exercise to the pelvic floor muscles. According to the characteristics of postpartum women pelvic floor muscles in women with postpartum 30 12-week pilates, Chinese health qigong Baduanjin training scheme of combining, in the form of personal training one to one, through the observation after the intervention of pelvic floor muscle strength index changes, aims to explore pilates joint eight brocade of female postpartum pelvic floor muscle exercise effect, which provides the theoretical basis for the training of such experimental plan. Methods: Literature, expert interview, experiment, questionnaire and mathematical statistics were used Thirty postpartum women were recruited as experimental subjects in Guangzhou UPilates Studio. The subjects were required to have no unexplained vaginal bleeding, acute vaginitis, malignant tumors, physical disabilities and mental diseases, and to participate in the training voluntarily. Thirty postpartum women were randomly divided into group A, B and C, with 10 in each group. Control group A received Pilates training, control group B received Baduanjin training, observation group C received Pilates combined with Baduanjin training. The three groups practiced for one hour each time, three times A week. The heart rate of group A and group C was controlled within the range of 50%-60% HRmax to ensure moderate and low intensity exercise. Group B maintained low intensity exercise. The subjects of the three groups were evaluated by using pelvic floor muscle training instrument. They went to the hospital for pelvic floor muscle strength assessment one day before the start of the experiment, the day after the end of the experiment, and four weeks after the end of the experiment at 2 o 'clock in the afternoon, and were operated by professionals in the hospital. Group A postpartum women: warm up for 5 minutes each time, Pilates postpartum movement exercises for 45 minutes, 10 minutes of stretching and relaxation. Group B: Postpartum women: Use Baduan Jin password version promoted by General Administration of Sport of China, practice Baduan Jin for 1 hour/class hour every day, practice for 4 times per class hour. Practice twice, rest for 5 minutes, and then proceed to the next round. Postpartum women in group C: 12-week three-stage training program process: manipulation release, manipulation activation, dynamic stretching, Pilates training, and Baduanjin exercise. Postpartum Pilates training movement design: the first 1-3 movements, dynamic activation of pelvic floor muscles. The last 4-21 movements strengthen the strength and endurance of pelvic floor muscles, gluteal muscles and abdominal muscles, improve the range of motion, physical coordination, and flexible spine. Each training process: warm up for 5 minutes, Pilates exercises for 43 minutes, 12 minutes of 8 Kam training. One-on-one instruction by a professional coach. (1) Test indicators: pelvic floor muscle strength. (2) Testing instrument: pelvic floor muscle training instrument (Changzhou Ruihai Yingnuo Medical Technology Co., Ltd.). (3) Test method: the subjects emptied feces and urine, lay flat on the bed to take the bladder lithotomy position, and then put the probe into the vagina with a condom. Then according to the doctor's instructions to contract and relax the pelvic floor muscles, the final result. Three groups of postpartum women were investigated. The content of the survey was ICI-Q-SF short form rating scale, which was distributed by using the small program of questionnaire. Thirty subjects were distributed three times: 1 day before the experiment, after the experiment, and 4 weeks after the experiment. Results: 1. Multiple comparison of ICI-Q-SF scores of postpartum women in the three groups after the experiment: there was no difference between group A and group C after the experiment and four weeks after the experiment (P>0.05). P values between groups A, C and B were all less than 0.01, which was statistically significant. 2. According to ANOVA analysis, the ICI-Q-SF scores of postpartum women in the first three groups were all greater than 0.05, which was of research significance. After the experiment with the experimental one month after three sets of postpartum women ICI - Q - SF, scores are higher than before the trial, A and group C after the experiment and experimental around scores than group B after 4 weeks after experiment and after experiment score is high, the observation group C with 4 weeks after experiment after experiment score more than 4 weeks after experiment and after experiment group A high score, P values A and C group were less than 0.01, has A very significant difference. 3. Multiple comparison of pelvic floor muscle strength among the three groups after the experiment: there was no difference between group A and group C after the experiment and four weeks after the end of the experiment (P>0.05). P values between groups A, C and B were all less than 0.01, which was statistically significant. 4. ANOVA analysis showed that the pelvic floor muscle strength of postpartum women in the first three groups was all greater than 0.05, which was of research significance. After the experiment and four weeks after the experiment, the pelvic floor muscle strength values of postpartum women in the three groups were all higher than that before the experiment. The pelvic floor muscle strength values of group A and C were all higher than that of group B after the experiment and four weeks after the experiment, and the pelvic floor muscle strength values of group C were all higher than that of group A after the experiment and four weeks after the experiment. Conclusion: The three training programs in the experiment can all improve the symptoms of postpartum stress urinary incontinence in women, and to some extent can improve the muscle strength of pelvic floor. Pilates is better than Baduanjin training, and Pilates combined with Baduanjin training has the best effect. In the future personal trainer training process, we should pay attention to the combination of Chinese and Western, diversification, individualization and refinement, improve the professional quality level of coaches, and scientifically guide postpartum women to carry out rehabilitation exercise in today's three-child comprehensive opening. At the same time, the society and the family should also pay attention to and strengthen the cognitive level of postpartum women, so that they are aware of the importance of pelvic floor muscle repair. Finally, the hospital should increase the cooperation with fitness clubs and studios, and provide high-quality private customized services according to the needs of customers to ensure that puerpera can get targeted treatment and rehabilitation. Due to the particularity of the experimental subjects, the sample size of this experiment is small, which is the limitation of this experiment.